2005
DOI: 10.1590/s0102-311x2005000300010
|View full text |Cite
|
Sign up to set email alerts
|

Relação do índice de massa corporal, da relação cintura-quadril e da circunferência abdominal com a mortalidade em mulheres idosas: seguimento de 5 anos

Abstract: Relação do índice de massa corporal, da relação cintura-quadril e da circunferência abdominal com a mortalidade em mulheres idosas: seguimento de 5 anos Relationship between body mass index, waist circumference, and waist-to-hip ratio and mortality in elderly women: a 5-year follow-up study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
22

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
2
13
0
22
Order By: Relevance
“…The present study showed a high prevalence of systemic arterial hypertension (SAH) (80.4%), higher than that found in the North-American population 13 and in Brazilian epidemiological studies, which showed a prevalence of SAH between 39% and 72.5% among the elderly [14][15][16][17] . The results of the Framingham study confirm that the prevalence of SAH tends to increase with age, but in the last four decades, there was no decrease in the prevalence of SAH, in spite of the progress achieved concerning its detection and treatment 18 .…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The present study showed a high prevalence of systemic arterial hypertension (SAH) (80.4%), higher than that found in the North-American population 13 and in Brazilian epidemiological studies, which showed a prevalence of SAH between 39% and 72.5% among the elderly [14][15][16][17] . The results of the Framingham study confirm that the prevalence of SAH tends to increase with age, but in the last four decades, there was no decrease in the prevalence of SAH, in spite of the progress achieved concerning its detection and treatment 18 .…”
Section: Discussionmentioning
confidence: 61%
“…That occurs due the interruption in the habit of smoking with the aging process, the presence of morbidities, the differences between generations or the premature death of smokers. However, elderly smokers, when compared to younger smokers, present a higher risk of developing diseases related to smoking, as they tend to present a longer and more intense exposure to tobacco 17 …”
mentioning
confidence: 99%
“…Observamos que 38,4% dos idosos entrevistados relataram tabagismo. Esse é um resultado preocupante, pois exposições longas e intensas ao tabaco 21 , associadas ao processo de envelhecimento, induzem maior risco de desenvolvimento de doenças relacionadas ao tabagismo. O resultado desse estudo foi superior ao encontrado em estudos realizados com idosos em Goiânia (10,0%), em Bambuí (19,6%) 17 , em Pelotas (14,4%) 18 e na amostra brasileira (12,7%) 19 .…”
Section: Discussionunclassified
“…Several investigations have shown that WC is an indicator of central obesity in adults and elderly women 1,[8][9][10][11][12]21,23,33 , consequently it is directly associated with health risks 17,18,34 . Additionally, WC has a greater predictive cutoff point for hypertension than BMI in men 19 and mainly in the first WC cutoff point (WC ≥80) in adult women 14 , WC has an odds ratio for hypertension of 1.76 between 80-88cm and OR 2.18 for WC ≥88cm 13 , and it is a strong predictor of CVD in women aged 25 to 74 years 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Although central obesity has been shown to alter the cardiovascular, renal, and metabolic systems, triggering inflammatory responses, the cause-effect relationship between adiposity and hypertension is not quite understood. However, it is common agreement that individuals with elevated central adiposity have an increase in the risk for hypertension, cardiovascular disease and mortality 3,6,[8][9][10][11][12] . Additionally, central obesity has been strongly associated with a high prevalence of hypertension 6,[8][9][10][12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%